UPAYA KANTOR IMIGRASI I KOTA PEKANBARU DALAM MENANGANI IMIGRAN ILLEGAL ASAL BANGLADESH DI PULAU RUPAT - Mahdi, Arjuna; Takwa, Tuah Kalti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to analyze the efforts of the Pekanbaru Class I Immigration Office in handling illegal immigrants from Bangladesh. The research method used is a qualitative approach with data collection techniques through interviews and field observations. This study utilizes public policy theory because it can explain how government policies, particularly those related to handling illegal immigration, are formulated, implemented, and evaluated. The results show that the Pekanbaru Immigration Office has taken various strategic steps, such as strengthening immigration supervision at regional entry points, collaborating with other law enforcement agencies, and increasing early detection through patrols and document checks. In addition, the immigration office also carries out administrative immigration actions, such as detention and deportation of illegal immigrants proven to have violated statutory provisions. Therefore, cross-sectoral synergy and increased institutional capacity are needed to address the problem of illegal immigration more effectively and sustainably. Keywords: Illegal immigrants, Pekanbaru Immigration Office, Bangladesh, law enforcement, immigration